The Influence of Built Form and Area on the Performance of Sustainable Drainage Systems (SuDS) (Future Cities and Environment, 2021)
In the face of increased housing demand and climatic change, sustainable urban drainage systems (SuDS) are often viewed as an alternative to traditional piped drainage networks, offering multiple benefits. However, whilst design guidelines for SuDS exist, there is little systematic understanding of how SuDS perform for different urban forms at a neighbourhood scale. This paper, therefore, explores the response of a one hectare urban area to rainfall events of varying magnitude under a range of different scenarios for the built environment (development density, SuDS type, residence type and SuDS deployment extent), using the Stormwater Management Model (SWMM). It finds that whilst increased development density leads to an increased peak runoff rate, in some cases lower SuDS deployment in higher density scenarios leads to lower runoff rates than higher deployment in a lower development density. The type of SuDS also has a considerable impact on runoff dynamics, with those constructed on existing infrastructure offering greater proportional reductions in runoff rates than those constructed on previously undeveloped land.